The development of school theatre pedagogy in Lithuania: aspect of ideas - Kazragytė, Vida (Pedagogika, 2014)
At the beginning of last century the school theatrical performances were organized by enthusiastic teachers amateurs. The purposes of theatre in schools were considered differently: as a teaching tool and as area of artistic education through theatre. From the 8th decade of XX century in Klaipėda in higher school the preparing of stage directors for amateur activities was established. There the professional actors worked as theatre teachers. Thy pushed the artistic trend toward. But the idea of children‘s theatre as a learning tool through performances grounded on pretend play was also strong. About 1500 of children‘s theatrical groups aroused in Lithuania. From 1988 the reform of general education started and through about twenty years the theatre subject or acting was integrated in the system of general education in Lithuania. In 2003 the implementation of theatre pedagogy master study program and in 2005 bachelor study program undertakes. But until now there are no theoretical backgrounds of theatre didactics created. But on the development of didactics the quality of theatre integration in general education depends. In 2013 the theatre mature examination was implemented firstly. It requires the new competences of theatre teachers. And that is the new directions for theatre pedagogy development.